CD5 is phosphorylated on tyrosine after stimulation of the T-cell antigen receptor complex. - Davies, A A (1992)
When T cells are activated by the T-cell antigen receptor, a number of cellular proteins are phosphorylated on tyrosine. We investigated whether any of these proteins were present on the surface of activated T cells. Using the human leukemic T-cell line Jurkat and normal peripheral blood lymphocytes, we identified a 67-kDa cell surface glycoprotein in anti-phosphotyrosine immunoprecipitates, after treatment of the cells with CD3 antibody. When cell lysates were depleted of CD5 by sequential immunoprecipitation, the 67-kDa phosphotyrosyl polypeptide was no longer precipitated by the phosphotyrosine antibody. Western blot analysis of anti-phosphotyrosine precipitates confirmed that this glycoprotein was CD5. It was possible that CD5 was present in the anti-phosphotyrosine immunoprecipitates due to its physical association with phosphotyrosyl proteins rather than being directly tyrosine-phosphorylated itself. However, Western blot analysis of anti-CD5 immunoprecipitates with phosphotyrosine antibody and phosphoamino acid analysis demonstrated that CD5 was indeed phosphorylated on tyrosine after stimulation of the cells with CD3 antibody and was concomitantly phosphorylated on serine and threonine. Tyrosine phosphorylation of CD5 was maximal 2 min after CD3 stimulation and returned to baseline levels by 60 min. CD5 is expressed on the cell surface of all mature T cells and a small proportion of B lymphocytes and has recently been identified as the ligand for CD72, a receptor present on the surface of all B cells. The present data suggest that tyrosine phosphorylation may be involved in B-cell-T-cell communication.